Safety Evaluation of Nanotechnology Products - Abraham J. Domb; Ghorbanali Sharifzadeh; Victoria Nahum; Hossein Hosseinkhani (MDPI AG, 2021)
Nanomaterials are now being used in a wide variety of biomedical applications. Medical and health-related issues, however, have raised major concerns, in view of the potential risks of these materials against tissue, cells, and/or organs and these are still poorly understood. These particles are able to interact with the body in countless ways, and they can cause unexpected and hazardous toxicities, especially at cellular levels. Therefore, undertaking in vitro and in vivo experiments is vital to establish their toxicity with natural tissues. In this review, we discuss the underlying mechanisms of nanotoxicity and provide an overview on in vitro characterizations and cytotoxicity assays, as well as in vivo studies that emphasize blood circulation and the in vivo fate of nanomaterials. Our focus is on understanding the role that the physicochemical properties of nanomaterials play in determining their toxicity.